EFFECTS AEROBIC EXERCISE ON VO2 MAX IN PHASE 2 REHABILITATION POST PERCUTANEOUS CORONARY INTERVENTION (PCI) AT DR. MOEWARDI HOSPITAL - Nurrahman, Muhammad Rizqa; Naufal, Adnan Faris; Susilo, Ridwan Andi (Universitas Muhammadiyah Surakarta, 2021)
Introduction Coronary Heart Disease (CHD) is a disease that occurs due to the formation of atherosclerotic plaques in the lumen of blood vessels. Case Presentation: Aerobic exercise was carried out for 2 months and evaluated every month. Aerobic exercise is carried out based on the Cardiovascular Rehabilitation Manual compiled by the Indonesian Association of Cardiovascular Specialists. Based on the Cardiac Rehabilitation Manual, patients who will be given aerobic exercise are examined first using the 6 minute walking test to determine the dose to be used for exercise. Exercise intensity using the target Heart Rate Reserve (HRR). Management and Outcome: Aerobic exercise can increase VO2 Max from before being given aerobic exercise until the second month evaluation. This proves that Aerobic exercise can increase VO2 Max in coronary heart patients after Percutaneous Coronary Intervention. Discussion: The mechanism underlying the increase in VO2Max due to the intensity of aerobic exercise in the elderly is an improvement in the adaptation mechanisms at the central and peripheral levels to exercise. The increase in VO2Max that occurs after endurance training in healthy elderly men is due to an increase in peak stroke volume and a lower CO difference, thereby increasing A-VO2Max.. Conclusion: After the patient on behalf of Mrs. S carried out a phase 2 rehabilitation program with Aerobic exercise or walking exercise for 2 months, the results obtained were a fairly good increase in VO2 Max in post-Percutaneous Coronarry Intervention patients.